2014
DOI: 10.1371/journal.pone.0094124
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia Is Associated with Acute Respiratory Distress Syndrome Mortality: An International Study

Abstract: BackgroundEarly detection of the Acute Respiratory Distress Syndrome (ARDS) has the potential to improvethe prognosis of critically ill patients admitted to the intensive care unit (ICU). However, no reliable biomarkers are currently available for accurate early detection of ARDS in patients with predisposing conditions.ObjectivesThis study examined risk factors and biomarkers for ARDS development and mortality in two prospective cohort studies.MethodsWe examined clinical risk factors for ARDS in a cohort of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 39 publications
9
51
0
Order By: Relevance
“…The meaning of the PDMP/Plts ratio should be considered. A higher PDMP/Plts ratio might be a consequence of the association between thrombopenia and mortality, as previously reported [35][36][37] . The PDMP/Plts ratio is elevated as a result of a decreased platelet count.…”
Section: Conflicts Of Interestsupporting
confidence: 69%
“…The meaning of the PDMP/Plts ratio should be considered. A higher PDMP/Plts ratio might be a consequence of the association between thrombopenia and mortality, as previously reported [35][36][37] . The PDMP/Plts ratio is elevated as a result of a decreased platelet count.…”
Section: Conflicts Of Interestsupporting
confidence: 69%
“…[20,[23][24][25][26][27] There have been reports indicating that the rate of platelet decline or recovery from thrombocytopenia may have important prognostic value in diseases such as sepsis and acute respiratory distress syndrome (ARDS). [21,22,24,26] Our study had several limitations. Firstly, this study was conducted at a single tertiary care centre in a northern part of India.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia is the most common coagulation problem in the ICU, and is generally caused by the following mechanisms: increased destruction or consumption of platelets, decreased production, dilution, and sequestration of platelets (30,31). Clinical events related to these mechanisms, such as disseminated intravascular coagulation, trauma, or massive transfusions, are considered risk factors that affect ARDS outcomes (7,32,33). Thus, treatments for thrombocytopenia might have benefits for patients with ARDS, whereas the treatments should be given in respect to the etiology (34).…”
Section: Discussionmentioning
confidence: 99%
“…For example, worsening oxygenation, multiple organ dysfunction, and progressive underlying diseases are common risk factors for ARDS mortality (4). Recently, platelets have been increasingly recognized for their roles in ARDS outcomes, which are likely mediated by their involvement in inflammatory responses and disseminated intravascular coagulation (5)(6)(7). Genetic risk factors may also determine ARDS outcomes (8); studies have identified a few potential prognostic biomarkers (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%